Crowdsourcing Field Observations from Smallholder Farmers in Tanzania Using Interactive Voice Response. (1st June 2019) - Chancellor, Tim; Priebe, Jan; Mkenda, Prisila
The term crowdsourcing was first used in 2006 but the approach has been employed in various fields over a much longer period of time. The central idea is to collect information from a large number of people in order to achieve a common goal such as to increase knowledge, solve a problem or enhance the efficiency of a process. In the realm of research, crowdsourcing is closely connected with citizen science in which members of the public are engaged in a scientific project. In C17th England, the naturalist John Ray arranged for a large number of volunteers to collect specimens for him and there are datasets on the phenology of plants, birds and insects in England and in some other countries which provide a continuous record for hundreds of years. A current example of how non-specialists are helping to gather large quantities of biological data is the Breeding Bird Survey run by the British Trust for Ornithology which engages thousands of volunteers to submit records of over 200 bird species each year. Although crowdsourcing has been widely used in environmental monitoring there are few examples of its use in agriculture. This is surprising because there is a tradition of participatory approaches to agricultural research which have been developed in recent decades. The potential for harnessing large numbers of individual farmers to generate information on the performance of crop varieties in different locations was recently demonstrated through a triadic comparison of technologies. This was taken a stage further in a subsequent study in which a total of 12, 409 farmers collected data on experimental plots of common bean (Phaseolus vulgaris) in Nicaragua, durum wheat (Triticum durum) in Ethiopia, and bread wheat (Triticum aestivum) in India. The results showed that expected effects of seasonal climatic variables on the performance of the crop varieties occurred and that these were generalizable across growing seasons. The authors concluded that their approach allows for more targeted recommendations for the deployment of crop varieties and that these may differ substantially from recommendations derived from current evaluation procedures in which testing is done at a limited number of sites. Crowdsourcing has tremendous potential for use in insect pest management. Up to date information on the distribution and abundance of insect pests of crops is needed for the development of appropriate management strategies. Field surveys can be used to identify locations where pest levels are high and sequential monitoring may help to establish seasonal patterns of occurrence. Surveys are also useful in monitoring the likely sources of migrant pests and recording their dispersal from these areas. When used in combination with other information such as climatic data, field surveys are an essential element of insect pest forecasting systems. In developing countries, field surveys are generally conducted by agricultural research and extension staff. Their main limitation is that they are labour-intensive and costly to carry out. Since resources of manpower and funds are limited, surveys are carried out infrequently and in restricted locations which may not be representative of the situation over larger areas. As a result national agricultural research and extension systems are constrained by having limited access to accurate information on the status of insect pests in different locations. This makes it difficult for them to respond to new threats such as the recent appearance and spread of the fall armyworm (Spodoptera frugiperda) in Africa where monitoring and early warning systems are crucial for effective control.